2021
DOI: 10.1200/jco.2021.39.15_suppl.e16001
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral T cell clonality and survival in a randomized phase II study of preoperative autophagy inhibition in combination with gemcitabine and nab-paclitaxel treatment in patients with resectable pancreatic cancer.

Abstract: e16001 Background: Autophagy is a cell survival mechanism that is upregulated in pancreatic ductal adenocarcinoma (PDAC). PDAC autophagy results in an altered metabolic phenotype that promotes tumor progression, chemotherapeutic resistance, and immune evasion. Methods: We previously completed a randomized phase II clinical trial of preoperative gemcitabine-nab-paclitaxel with (PGH n = 34) and without (PG, n = 30) autophagy inhibition in patients with resectable and borderline resectable PDAC, which demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Both compounds have been used in several clinical trials to target various cancers, including PDAC [116]. Although HCQ showed only minimal activity when used as monotherapy [126], HCQ plus GnP significantly improved the response rates compared with GnP alone (21% vs. 38%, p = 0.047) [127], showed an improved pathological response, and increased immune cell infiltration [103,104](NCT01978184), further confirming the role of autophagy as a key resistance mechanism against therapeutic treatment. Based on these findings, multiple clinical trials are ongoing to test the efficacy of combining autophagy/lysosome inhibitors (mainly HCQ) with conventional chemotherapy, targeted therapy, and ICB (Table 2).…”
Section: Clinical Trials Targeting Autophagy In Pdacmentioning
confidence: 81%
See 1 more Smart Citation
“…Both compounds have been used in several clinical trials to target various cancers, including PDAC [116]. Although HCQ showed only minimal activity when used as monotherapy [126], HCQ plus GnP significantly improved the response rates compared with GnP alone (21% vs. 38%, p = 0.047) [127], showed an improved pathological response, and increased immune cell infiltration [103,104](NCT01978184), further confirming the role of autophagy as a key resistance mechanism against therapeutic treatment. Based on these findings, multiple clinical trials are ongoing to test the efficacy of combining autophagy/lysosome inhibitors (mainly HCQ) with conventional chemotherapy, targeted therapy, and ICB (Table 2).…”
Section: Clinical Trials Targeting Autophagy In Pdacmentioning
confidence: 81%
“…In line with this, a recent clinical trial using HCQ and gemcitabine plus nabpaclitaxel (GnP), a standard-of-care chemotherapy for PDAC [102], as neoadjuvant chemotherapy (NCT01978184), showed that the addition of HCQ increased the number of tumor-infiltrating CD8 ? T cells [103,104]. Additionally, a recent study identified tumorcell-derived progranulin (PGRN) as a driver of autophagydependent MHC-I degradation and subsequent immune evasion [105].…”
Section: Autophagy Facilitates Immune Evasion Across Cancer Typesmentioning
confidence: 99%
“…In 2020, another randomized phase II trial was conducted to compare the efficacy of HCQ plus GnP and GnP alone in preoperative chemotherapy. An analysis of resected tumor specimens demonstrated an improved pathological response and increased tumor-infiltrating immune cells, including CD8 + T cells [ 138 , 139 ] (NCT01978184), supporting the role of autophagy as a driver of immune escape in PDAC [ 136 , 137 ]. Based on these findings, multiple clinical trials are ongoing to test the therapeutic efficacy of combining HCQ with conventional chemotherapy, molecular-targeted therapy, and ICB ( Table 1 ).…”
Section: Nutrient Scavenging Pathways In Pdacmentioning
confidence: 99%
“…Importantly, genetic or pharmacological inhibition of autophagy restores cell surface MHC-I expression and antigen presentation in PDAC cells, leading to increased CD8 + T cell infiltration, reduced tumor burden, and improved response to ICB in syngeneic tumor transplant mouse models [ 136 , 137 ] ( Figure 5 ). Consistently, a recent clinical trial demonstrated that the addition of HCQ to gemcitabine plus nab-paclitaxel (GnP), a standard-of-care chemotherapy for PDAC [ 6 ], in the context of neoadjuvant chemotherapy leads to increased CD8 + T cell infiltration in resected tumors [ 138 , 139 ]. In line with these findings, a recent study identified cancer cell-derived progranulin (PGRN) as a driver of autophagy-dependent MHC-I degradation and subsequent immune evasion [ 140 ].…”
Section: Nutrient Scavenging Pathways In Pdacmentioning
confidence: 99%